Pengaruh Profesionalitas Guru Terhadap Kinerja Guru Di Madrasah Aliyah Kejuruan (MAK) Madani Manado - Abdullah, Armin (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
The education process in madrasas is always changing and developing in line with the increasing competence and professionalism of teachers in the implementation of education in madrasas. The same challenge is also faced by Vocational Madrasah Aliyah in integrating Islamic educational values ​​and nursing productive curriculum. So as a strategic step and a solution, the author tested the influence of teacher professionalism on teacher performance at Madrasah Aliyah Kejuruan Madani Manado. The method that the author uses in this study is a quantitative method. The research sample was madrasa teachers, totaling 30 respondents in the research population. The research instrument used a questionnaire and hypothesis testing was carried out through a simple linear regression analysis test. The results of the study stated that there was a significant and positive effect of teacher professionalism on teacher performance at Madrasah Aliyah Kejuruan Madani Manado, thus Ha was accepted. The power of influence in the strong category is 0.687 and the contribution given by teacher professionalism to teacher performance is 47.2%. The more effective the improvement of teacher professionalism, the more the performance of teachers at Madrasah Aliyah Kejuruan Madani Manado will increase.